Etika Komunikasi Dharmaduta di Kecamatan Keling, Kabupaten Jepara menurut Kemurnian Ucapan dalam Cunda Sutta - Okta Adhiviyanto, Dirga Yuka; Sadtyadi, Hesti; Wardani, Niken (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2025)
Communication based on ethics can strengthen trust between individuals, foster mutual respect, and create an inclusive dialogical atmosphere. This article aims to examine how the four purities of speech in the Cunda Sutta can be used as a basis for communication ethics for Dharmaduta in carrying out their duties in Keling District, Jepara Regency. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Cunda Sutta becomes the foundation of communication ethics for Dharmaduta in carrying out their duties. Dharmaduta provides information and conveys teachings in accordance with what is needed by the people and based on facts without providing additions and exaggerations, Dharmaduta uses Javanese language, namely fine krama language and adjusts to the audience present, Dharmaduta provides support to the people to carry out interfaith activities, for example by helping the smooth running of the traveling takbir activities to welcome Eid al-Fitr. In the discussion session, Dharmaduta invites people to discuss about the teachings of Buddhism and does not discuss the shortcomings of others. This research shows that integrating the teachings of the Cunda Sutta in Dharmaduta's communication practices not only strengthens Dharmaduta's religious role, but also becomes a real contribution in maintaining the values of diversity and maintaining social harmony at the local level. Through a communication approach that prioritizes honesty, unity, gentleness, and usefulness, Dharmaduta is able to foster tolerance and prevent inter- religious conflicts.